2022
DOI: 10.1111/bjh.18547
|View full text |Cite
|
Sign up to set email alerts
|

Safety of coronavirus disease 2019 vaccines in 213 adult patients with sickle cell disease

Abstract: Summary Given the lack of information about safety of the COVID‐19 vaccines for sickle cell disease (SCD) patients, we sought to determine whether COVID‐19 vaccine was associated with subsequent hospital admission for vaso‐occlusive events (VOEs). We included 402 patients with SCD, including 88 regularly transfused. As of July 31, 2021, 213 (53.0%) of them had received a least one dose of COVID vaccine (Pfizer 93.0%). We showed similar risk of hospital admission for a VOE among vaccinated patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our SCD cohort from a sickle cell center in Paris, only 48.9% were vaccinated against COVID-19; this is much lower than the value of 72.3% observed for the age group 18-39 years in the general population. 15 During pregnancy, a fear of harming the fetus might add to ethnic and cultural factors, resulting in an estimated vaccination rate around 65.7%, which is lower than that in the general population. 16 In conclusion, our results emphasize the need to monitor and manage COVID-19 during pregnancy carefully, particularly in women with SCD.…”
Section: Letter To the Editormentioning
confidence: 99%
“…In our SCD cohort from a sickle cell center in Paris, only 48.9% were vaccinated against COVID-19; this is much lower than the value of 72.3% observed for the age group 18-39 years in the general population. 15 During pregnancy, a fear of harming the fetus might add to ethnic and cultural factors, resulting in an estimated vaccination rate around 65.7%, which is lower than that in the general population. 16 In conclusion, our results emphasize the need to monitor and manage COVID-19 during pregnancy carefully, particularly in women with SCD.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Given these data, several reports have suggested that patients with SCD are at increased risk of severe COVID‐19 infection and may warrant the distinct vaccination schedules recommended for immunocompromised patients 3 . However, efficacy and safety data for COVID‐19 vaccination in SCD is limited 4–6 . Furthermore, studies have failed to detect different outcomes for COVID‐19 infection in patients with SCD when controlled for co‐morbidities and end‐organ damage, 7 suggesting that the overall response to COVID‐19 vaccination may not significantly differ from the general population.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, efficacy and safety data for COVID-19 vaccination in SCD is limited. [4][5][6] Furthermore, studies have failed to detect different outcomes for COVID-19 infection in patients with SCD when controlled for co-morbidities and…”
mentioning
confidence: 99%
“…1,2 Additionally, COVID-19 vaccines were reported to be safe in patients with SCD. 3,4 Even though the B.1.1.529 (Omicron) variant seems to induce milder forms of infection in the general population, [5][6][7] few data exist on COVID-19 outcomes among adult patients with SCD during the Omicron wave. The objectives of our study were to describe the course of COVID-19 among adult patients with SCD during the Omicron wave and to compare clinical outcomes according to vaccination and/or past COVID-19 infection status.…”
mentioning
confidence: 99%